Bad Liar : a Novel - Hoag, Tami (New York : Dutton, 2024)
"Small-town labels are hard to shake. Hometown hero. Fallen angel. Can anyone ever escape their past? A murder victim dumped at the dead end of a lonely country road, face and hands obliterated by a shotgun blast, is not the way sheriff's detective Nick Fourcade wants to start his week. His only lead takes him to the family of a hometown hero suddenly gone missing. Marc Mercier left his home for a weekend hunting trip and hasn't been seen since. Meanwhile, sheriff's detective Annie Broussard begins her first day back on the job after suffering a brutal attack by taking on the case of B'Lynn Fontenot, a mother desperate to find her grown son, a recovering drug addict. Robbie Fontenot has been missing for eight days, but the local police have no interest in the case, telling B'Lynn that an adult has the right to disappear, and a missing addict is no big surprise. But B'Lynn swears her son was turning his life around. Sympathetic to a mother's anguish, Annie agrees to help B'Lynn, knowing she's about to start a turf war with the city police. As Annie searches for Robbie Fontenot and Nick investigates the disappearance of Marc Mercier, it quickly becomes apparent that nothing is as it seems in the lives of either man. And it's still not clear whether either--or neither--of them might be the unidentified murder victim. Old jealousies and fresh deceits, family loyalties gone wrong and love turned sour all lay a twisting trail that leads deep into the Louisiana swamp, endangering all who cross the path of a bad liar"--
Keywords: Detective and mystery fiction; Novels